Relevansi Regulasi Pertambangan Internasional dengan Penanganan Covid-19 di Indonesia - Nasir, Melisa; Hardianti, Inas; kholiyah, Elmi; Fitriani, Fitriani; Tobing, Imanuel CML (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Pressure on the mining industry was caused by global mining activities which experienced disruptions to the demand for and sales of mining materials during the COVID-19 pandemic. The consequences of these events affected world mining production. The purpose of this article is (1) Many small people in the world have not applied the principles of "good mining practices" (2) Unlicensed Mining (PETI) in Indonesia has not paid attention to the National Law and the Principles of Sustainable Development (3) Unlicensed Mining Policy During the Covid-19 Pandemic. The result of this scientific work is that small-scale gold mining using mercury and cyanide has been practiced internationally, namely in America, Australia and several other countries since the 1800s. In North America, gold rush activities, 180 years ago, were concentrated in the California region. A total of 2,471 Indonesian locations, namely mining for both minerals and coal, were carried out without permits, in this case, Unlicensed Mining (PETI). The state, government and all stakeholders are obliged to protect and manage the environment in the implementation of sustainable development so that the Indonesian environment can remain a source and support for life for the Indonesian people and other living things.